How to speak Dragonese - Cowell, Cressida (New York : Hodder Children's Books, 2005)
Recounts the further escapades of Hiccup Horrendous Haddock the Third as he continues his Viking training during which he escapes from a boatload of Roman soldiers and searches for his kidnapped dragon.
Z
910
Z
Keywords: Vikings -- Fiction; Pirates -- Fiction; Dragons -- Fiction; Humorous stories